Aksesibilitas Ibadah bagi Difabel: Studi atas Empat Masjid di Yogyakarta - Arif Maftuhin (INKLUSI, 2014)
This study was inspired by a project in the United States called “accessible congregation”, a project that promotes accessibility in the places of worshsip. While idea of “accessible congregation” is not less known in Indonesia, it is important to study how accessible are Indonesian mosques. Modifying what are considered to be more relevant indicators of accessibility for mosques in Indonesia, this researh studies four main mosques in Yogyakarta. This study found that most mosques are not acceessible and one mosque are less accessible, meaning that no mosque in Yogyakarta are fully accessible.1